Long- and Short-Term Stability of All Polarization-Maintaining Thulium Doped Passively Mode-Locked Fiber Lasers with Emission Wavelengths at 1.95 μm and 2.07 μm - Cuadrado Laborde, Christian Ariel (2023)
Featured Application: cutting/engraving/welding of plastics, laser scalpels, eye-safe light detection and ranging (LIDAR), remote sensing, and real-time spectroscopy. In this work, we compare the operation of a passively modelocked polarization-maintaining emission in two thulium-doped fiber lasers pumped at 1561 nm, with emission at wavelengths of 1.951 μm in one case and 2.07 μm in the other. We obtained a sequence of light pulses at 15.6 MHz, whose temporal width was 81 ps at 1.95 μm, and a sequence of light pulses at 13.1 MHz, whose temporal width was 94 ps at 2.07 μm. Finally, we also measured the long-term stability of this setup during a 24-h operation, as well as the short-term stability in a simulated harsh environment. The results confirm the superior performance of fiber laser systems with a fully polarization-maintaining design.